Efektivitas Intervensi Mindfulness-Based Childbirth Parenting (MBCP) bagi Ibu Hamil terhadap Kesejahteraan Psikologis Ibu: Sebuah Tinjauan Sistematis - Riska Adellia; Imami Nur Rachmawati; Titin Ungsianik; Hening Pujasari (Journal of Pharmaceutical and Sciences, 2026)
Background: Pregnancy is a critical life stage characterized by physiological and psychosocial changes that increase vulnerability to mental health disorders such as depression, anxiety, and fear of childbirth. Objective: To identify Mindfulness-Based Childbirth and Parenting (MBCP) as an intervention for reducing depression, anxiety, stress, and fear of childbirth, as well as enhancing prenatal attachment. Methods: This systematic review followed the PRISMA guidelines to analyze and present findings from randomized controlled trials (RCTs) involving pregnant women who received MBCP or other mindfulness-based interventions during pregnancy and reported outcomes related to mental health or prenatal attachment. Studies published in English between 2020 and 2025 were considered. Observational studies, reviews, and research without relevant outcomes were excluded. Literature searches were conducted in PubMed, ScienceDirect, ProQuest, Scopus, and ClinicalKey. Methodological quality was assessed using the JBI Critical Appraisal Checklist for RCTs. Due to heterogeneity in interventions and outcomes, meta-analysis was not feasible. A narrative synthesis was performed by summarizing study characteristics and thematically grouping results. Results: Ten RCTs (N=907) consistently demonstrated reductions in depression, anxiety, stress, and fear of childbirth, as well as improvements in prenatal attachment. Conclusion: MBCP interventions are effective in enhancing maternal psychological health and reducing fear of childbirth, with potential benefits for both mother and infant. Integration of MBCP into antenatal care and cultural adaptation is recommended. Further research is needed to evaluate long-term outcomes, cost-effectiveness, and implementation strategies across diverse contexts.